Study the percentage of infection with intestinal parasites in dogs in salahaldin prevence - Ashraf Jamal Mahmoud (Tikrit Journal of Pure Science, 2023)
The study examined 137 stray dogs from both sexes and aged 3 months - 3 years old, included 127 stray dogs and 10 dogs clinically normal, served as a control group. Clinical signs were observed, the percentage of infection with intestinal parasites was 49.60%, was diagnosed with worms Toxocara canis 32.28%, Toxascaris leonine 25.19%, and Taenia pisiformis 27.55%, and Moniezia sp. 37.79%, and Dipylidium caninum 19.68%, and Diphyllobothrium sp. 24.40% and oocysts each of Isospora spp. 13.38%, and Cryptosporidium spp. 16.53%. histopathological examination of the intestines showed transformation the columnor epithelial cells to the spherical or semi-spherical shape and also alienation the villi in the intestinal cavity, with the infilteration of large numbers of inflammatory white blood cells inside the core of the villi also appeared in the lamina propria,  agreat number of lymphocytes inflammatory cells with appearance of parasitic spherical cystic structures of worm Toxocara canis in the submucosal layer and between fibers of smooth muscle